Professional experience of midwives is not sufficient to accurately assess the amount of blood loss during labor - Kraśnianin, Elżbieta; Raba, Grzegorz; Kremska, Anna; Wróbel, Romana; Zych, Barbara (European Journal of Clinical and Experimental Medicine, 2018)
<p style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Postpartum hemorrhage is still one of the causes of maternal mortality and morbidity. The purpose of investigation was an examination of practical skills in blood loss assessment during labor by midwives. <p style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. To examine the practical skills of midwives that have different professional experience in blood loss assessment during labor. <p style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. A case-control prospective study of labour blood loss volume assessment with the use of a birthing simulator was conducted among midwives from 1 September 2016 to 30 May 2017. Midwives were divided in to 2 groups: Group I consisted of midwives who were recent university graduates without professional experience. Group II consisted of midwives with a minimum of two years of professional practice and assistance at more than 1000 births. This was a multicenter study. Outcome measures included visual evaluation of blood loss during simulation scenario. <p style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. Average evaluation of blood loss: Group I – 737 ml, Group II – 610 ml (p = 0.0002). There were no statistically significant differences between the groups in terms of diagnosing the cause of hemorrhage in the third stage of labor (p = 0.1503) neither in terms of identification of hemorrhage after perineal injury (p = 0.1503) . The examined midwives underestimated blood loss, however the midwives in Group I assessed blood loss statistically better. <p style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Subjective assessment of the amount of blood loss during labor is underestimated. Professional experience does not improve the accuracy of assessment of blood loss volume during labor.